2020
DOI: 10.1016/j.cattod.2019.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of hydrogen with flat (0001) and corrugated (11–20) and (10–12) cobalt surfaces: Insights from experiment and theory

Abstract: Highlights-H2 dissociation on Co is promoted by undercoordinated sites -But hydrogen atoms bind less strongly there compared to flat terrace sites -In FTS steps and kinks may be the dominant source of surface hydrogen atoms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The most stable adsorption on the (0001) surfaces of the hcp metals Co and Ru are the hollow hcp sites. Other theoretical studies identified the fcc sites as lowest energy positions but there are no significant energy differences to the hcp sites [107,[131][132][133]. The adsorption on the bridge sites (SB or LB) for (101 ̅ 0), and (112 ̅ 0)…”
Section: Hydrogen Adsorptionmentioning
confidence: 94%
“…The most stable adsorption on the (0001) surfaces of the hcp metals Co and Ru are the hollow hcp sites. Other theoretical studies identified the fcc sites as lowest energy positions but there are no significant energy differences to the hcp sites [107,[131][132][133]. The adsorption on the bridge sites (SB or LB) for (101 ̅ 0), and (112 ̅ 0)…”
Section: Hydrogen Adsorptionmentioning
confidence: 94%
“…It is interesting to note that the desorption peak temperature on the open Co(11–20) surface is significantly lower than on the close-packed Co(0001) surface. This shows that CO adsorption on cobalt is not necessarily stronger on surface atoms with a lower coordination number, unlike the situation on metals such as Ru and Pt where stronger adsorption on step sites was reported. , …”
Section: Resultsmentioning
confidence: 72%
“…CO desorption spectra from Co(11−20) (10 mm diameter and 1.5 mm thickness) and Co(0001) (8 mm diameter and 2 mm thickness) single crystal surfaces were obtained using a home-built vacuum system located at Syngaschem BV, as described in detail elsewhere. 35 The samples in this setup are mounted using a U-shaped W wire, which is in thermal contact with a liquid nitrogen reservoir so that sample temperatures of around 95 K can be reached. The samples are heated by passing a direct current through the support wire.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, Pt atom is selected as the single atom site to the host surfaces (M), on the M (111), M (100) and M (110) facets, except for cobalt host surface, where only the hexagonal close-packed Co (0001) surface is considered. Indeed, the (0001) surface is the main surface orientation of Co nanoparticles with hexagonal close-packed (HCP) bulk structure [32] which have been shown to have much higher intrinsic activity than the face centered-cubic (FCC)…”
Section: Segregation Energy ( ) and Environmental Segregation Energy ( )mentioning
confidence: 99%